Infotainment a ochrona prywatności osób powszechnie znanych - Zawadzka, Zofia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
This paper focuses on the personalization of information, in particular as regards commonly known individuals and the issue of privacy infringement. It should be indicated that tabloids and infotainment are characterized by mixing entertainment with news, paying more attention to people than to issues, and transforming social and human tragedies so they become a topic of public discussion for the purpose of providing entertainment. Information is now conveyed by means of human stories, concrete examples taken from the world of well-known people. This leads to the privacy of this category of people being infringed.